A model for coordinating and joint optimisation of inventory and credit policies in an inventory system with date–terms credit linked demand. (1st December 2014) - Aggarwal, K.K.; Tyagi, Arun Kumar
When firm gives credit period to its customers for generating credit sales in addition to cash sales, then it is quite possible that some of the cash customers would also take benefit of trade credit and buy on credit. Thus, decision of granting trade credit may have disintegrating effect on cash sales apart from stimulating new credit sales. Moreover, credit policy through its impact on demand becomes the determinant of inventory policy, which is intended to meet that demand. Therefore, inventory and credit policies are interrelated which should be determined simultaneously in a systems perspective. In this paper, a mathematical model is developed in discounted cash flow (DCF) framework to jointly determine inventory and credit policies in the presence of stimulating as well as disintegrating effect of credit period on demand. Numerical example and sensitivity analysis are presented to illustrate effectiveness of the model and results are discussed.